Remarks on the philosophy of Idokan Karate (Revista de Artes Marciales Asiáticas, 2019)
Every school of karatedo presents some special values and norms. May be, the philosophy of Idokan Karate is partially similar to other schools, and especially represents the Ido philosophy (that is not worldwide known). It is a real, practical philosophy, internalised and used by groups of karateka, as a form of today's warrior pathway. The author tries to answer the following questions: What ethics, values and rules are prominent in Idokan Karate? What is the specific, symbolic content of this style and school? This is a single case study, involving a content analysis of literature and the wider discourse, and the hermeneutic phenomenology. The study uses the analysis of broad discourse, which concerns both scientific studies and popularizing publications. Not without significance is the fact that the author has actively practiced Asian martial arts for over 40 years. The specific, symbolic content of Idokan Karate is taken from philosophic Taoism, Chinese and Japanese tradition of martial arts, and from Christianity. Its interpretation shows that the karate athlete has to go the moral way. It is the pathway toward being a better human. Such teleology comes from special values, rules and aims. In the normative ethics, the Decalogue and the idea of nobility (the Homo creator nobilis) are most important. Tao in Idokan Karate is understood as God's Word, the principle of love and the way of the Heavens.